the wind singer: book one in the wind on fire trilogy - Nicholson, William; William Nicholson
The Wind Singer (2000) by William Nicholson is a YA fantasy novel set in the strictly meritocratic city of Aramanth, where citizens are color-coded by performance. Kestrel Hath, defying this oppressive system, sets out with her twin, Bowman, and classmate, Mumpo, to find the voice of the ancient "Wind Singer" statue to save their city from the evil, mind-controlling
English